Effects on hybridization of interlayer composites and self-reinforced polypropylene - M. I., Ibrahim; M. R. M., Rejab; N. K., Romli; Quanjin, Ma; M. F., Rani (Faculty Mechanical Engineering, UMP, 2023)
In recent years, there has been increasing attention to develop a high-strength, lightweight composite as a potential substitution for conventional materials in various sectors, whereby most studies have focused on the mechanical performances of fibre-reinforced plastic (FRP) such as carbon, glass and aramid. In contrast, the hybrid composites are less common, though are viewed to have substantial potential in terms of flexibility and capability to merge the benefits of different composites. In this study, five composite designs consisting of several types of woven fibres and self-reinforced polypropylene (SRPP) sheets have been fabricated using the hand lay-up procedure. Several designs are arranged based on the interlayer hybridization mode. The static mechanical properties of the composite designs were examined through the standard tensile and three-point flexural tests. The outcomes attained from the experimental works revealed that carbon fibre-reinforced plastic (CFRP) produced the best tensile characteristics. The CFRP structure displayed 46% higher tensile strength and a 33% greater elastic modulus compared to the CAFRP specimen. Meanwhile, hybrid carbon/aramid fibre-reinforced plastic (CAFRP) pointedly enhanced flexural properties in comparison with single type and other hybrid composites, whereby CAFRP structure outperformed the CFRP structure, exhibiting superior results with variations of 50% and 19% in flexural strength and modulus, respectively. Though the inclusion of SRPP layers in-between the hybrid setup exhibited a decrease in both tensile and flexural strength, but improved the total strain level. The evidence from this study suggests that FRP composites indicate structures of high strength and stiffness but low elongation, whereas SRPP-based composites improve toughness but reduce stiffness characteristics.